2008
DOI: 10.2147/ndt.s2118
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic treatment with antiepileptic drugs modifies pentylenetetrazol-induced seizures in mice: Its correlation with benzodiazepine receptor binding

Abstract: Experiments using male CD1 mice were carried out to investigate the effects of subchronic (daily administration for 8 days) pretreatments with drugs enhancing GABAergic transmission (diazepam, 10 mg/kg, ip; gabapentin, 100 mg/kg, po; or vigabatrin, 500 mg/kg, po) on pentylenetetrazol (PTZ)-induced seizures, 24 h after the last injection. Subchronic administration of diazepam reduced latencies to clonus, tonic extension and death induced by PTZ. Subchronic vigabatrin produced enhanced latency to the fi rst clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The exact mechanism of epileptogenic action of pentylenetetrazole is still unclear, but it has been reported that PTZ produces seizures by inhibiting gamma-amino butyric acid (GABA) activity 17 .Due to the enhancement of GABAergic neurotransmission it has been shown to inhibit or attenuate seizure. Whereas the inhibition of GABAergic neurotransmission or activity is known to promote or facilitate seizure 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of epileptogenic action of pentylenetetrazole is still unclear, but it has been reported that PTZ produces seizures by inhibiting gamma-amino butyric acid (GABA) activity 17 .Due to the enhancement of GABAergic neurotransmission it has been shown to inhibit or attenuate seizure. Whereas the inhibition of GABAergic neurotransmission or activity is known to promote or facilitate seizure 18 .…”
Section: Discussionmentioning
confidence: 99%
“…[24] The possible mechanism of action of effective drugs may be enhancement of GABAergic neurotransmission such as Phenobarbital, Diazepam and tiagabine. [28] or through T-type calcium (Ca 2+ ) channels like ethosuximide. [29] In the present study, standard drug diazepam (2 mg/kg, i.p .)…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DRE needs to be carefully distinguished from other causes of therapeutic failure including tolerance development. Repeated administration of ASMs may cause pharmacodynamic or pharmacokinetic tolerance due to alterations in receptors, such as desensitization, downregulation, internalization, uncoupling from their signal transducers, or metabolic enzyme induction with consequent lower drug efficacy 114,115 . Pharmacokinetic studies support that phenytoin, carbamazepine, or phenobarbital upregulate efflux transporters in the brain and peripheral organs, affecting the bioavailability and disposition of ASMs 116 .…”
Section: Potential Mechanisms Of Drementioning
confidence: 99%
“…Repeated administration of ASMs may cause pharmacodynamic or pharmacokinetic tolerance due to alterations in receptors, such as desensitization, downregulation, internalization, uncoupling from their signal transducers, or metabolic enzyme induction with consequent lower drug efficacy. 114,115 Pharmacokinetic studies support that phenytoin, carbamazepine, or phenobarbital upregulate efflux transporters in the brain and peripheral organs, affecting the bioavailability and disposition of ASMs. 116 In this context, it is of interest that administration of ASMs can also result in epigenetic changes that negatively modify the course of the disease or may facilitate excitatory neurotransmission.…”
Section: Dre As a Multifactorial Phenomenonmentioning
confidence: 99%